Caesarean myomectomy: How safe it is? A retrospective analysis (Grande Medical Journal, 2024)
BackgroundLeiomyoma uterus not only causes menorrhagia, pain abdomen but also complicates pregnancy in various ways. The objectives of present analysis were to investigate the outcome in cases of pregnancy complicated by fibroids undergoing lower segment cesarean section (LSCS) in Grande International Hospital, Kathmandu Nepal.MethodFourteen cases of leiomyoma with pregnancy underwent LSCS with myomectomy following the delivery of the baby. The suturing of the uterus was done using vicryl no 1 and vicryl no 1 ‘0’ for closing the dead space after myomectomy. Continuous oxytocin infusion was given for next 12 hrs. The cases were analyzed for age of patient, parity, gestational age, an indication of LSCS, type of fibroid, size of fibroid, blood loss, duration of operation, and blood transfusions.ResultThirty-eight fibroids of various sizes (3-15cm) were removed from 18 women. The fibroid was on both anterior uterine walls with most being subserous and intramural. Mean blood loss (excluding cesarean section) was 76.1 ml and mean operative time (only myomectomy) was 26.1 mins. Three patients had a whole blood transfusion in post-operative period. No hysterectomy was required in any case.ConclusionMyomectomy during cesarean section is possible and safe in selected cases with proper indications and also with expert hands. It avoids a second surgery and its associated morbidity.